Diagnostic accuracy of anti-cyclic citrullinated Peptide antibodies in rheumatoid arthritis - Ali, Humaira; Alam, Junaid Mahmood; Nadeem, Ali; Naureen, Shazia (Pakistan Journal of Physiology, 2019)
Objective: To determine the diagnostic accuracy of anti-cyclic citrullinated peptide antibodies (Anti-CCP) in the diagnosis of rheumatoid arthritis (RA) in patients of joint pain keeping rheumatoid factor (RF) analysis, clinical and radiological features as the gold standard. Methods: A cross sectional study was performed at the Department of Chemical Pathology/Biochemical Laboratory Services, Liaquat National Hospital and Medical College, Karachi from January 2018 to June 2018. Over a period of six months, 363 samples of patients in the age group of 20–60 years having joint pain and suspected of suffering from rheumatoid arthritis were included after fulfilling inclusion and exclusion criteria. Patient demographics, age, sex, Anti-CCP results and RF levels were recorded. Results: There were 87 males and 283 females in the study. Sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and diagnostic accuracy were 69.2%, 98.5%, 97.8%, 77% and 84.2% respectively. Likelihood Ratio (LR)+ and LR- were 47 and 0.31 respectively. As per Receiver Operator Characteristic (ROC) curve analysis, the Area Under the Curve (AUC) is 0.839. The two-tailed test showed p<0.0001. The diagnostic accuracy of Anti-CCP antibodies in the diagnosis of Rheumatoid Arthritis in patients of joint pain was found to be 89.4%. The cutoff of anti-CCP was calculated by the Youden’s J. formula and was found to be 14 U/ml. Conclusion: Anti-CCP has a high sensitivity and specificity so it can be used for the diagnosis of rheumatoid arthritis in RF positive patients, which are common in Pakistan due to the high prevalence of Hepatitis C.